2020
DOI: 10.4028/www.scientific.net/kem.853.187
|View full text |Cite
|
Sign up to set email alerts
|

Study on Degradation Factor Adsorption Effect by Epoxy Resin with Functional Adsorbent

Abstract: As a countermeasure against deterioration of reinforced concrete structures that have suffered from salt damage, materials containing salt adsorbents have been developed. In this study, the basic properties of the “Hybrid Epoxy Resin Repair Agent” in which a functional adsorbent was added to an epoxy resin were grasped and verified. As a result, chloride ion adsorption effect assuming repair of salt damage and sulfate ion adsorption effect assuming chemical erosion repair was confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…From this kind of circumstance, it focused epoxy resin as an organic material was developed as an "epoxy resin repairing material by salt adsorption type " (from now on referred to as "repair material") by adding a salt adsorption agent to it. Previous studies confirmed the conventional quality of the epoxy resin used in this repair material and the corrosion prevention effect when applied to steel bars coated with salt [22][23][24].…”
Section: Introductionsupporting
confidence: 65%
“…From this kind of circumstance, it focused epoxy resin as an organic material was developed as an "epoxy resin repairing material by salt adsorption type " (from now on referred to as "repair material") by adding a salt adsorption agent to it. Previous studies confirmed the conventional quality of the epoxy resin used in this repair material and the corrosion prevention effect when applied to steel bars coated with salt [22][23][24].…”
Section: Introductionsupporting
confidence: 65%